Decision economics : in the tradition of Herbert A. Simon's Heritage : distributed computing and artificial intelligence, 14th International Conference /: in the tradition of Herbert A. Simon's Heritage : distributed computing and artificial intelligence, 14th International Conference. ([2018]) - Unknown
No abstract available